2022
DOI: 10.3389/fneur.2022.857654
|View full text |Cite
|
Sign up to set email alerts
|

Titrating the Translational Relevance of a Low-Level Repetitive Head Impact Model

Abstract: Recently, there has been increased attention in the scientific community to the phenomenon of sub-concussive impacts, those hits to the head that do not cause the signs and symptoms of a concussion. Some authors suggest that sub-concussive impacts may alter behavior and cognition, if sustained repetitively, but the mechanisms underlying these changes are not well-defined. Here, we adapt our well-established weight drop model of repetitive mild traumatic brain injury (rmTBI) to attempt to produce a model of low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Injury severity was moderate-to-severe TBI in 26 studies, smTBI in 15, and rmTBI in 7 studies. Twenty-six studies performed a longitudinal assessment of GFAP levels after TBI (41,42,5580).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Injury severity was moderate-to-severe TBI in 26 studies, smTBI in 15, and rmTBI in 7 studies. Twenty-six studies performed a longitudinal assessment of GFAP levels after TBI (41,42,5580).…”
Section: Resultsmentioning
confidence: 99%
“…There was an exception in one study using a weight drop injury model that reported increased GFAP levels at 30d post-injury (73). In rmTBI models, GFAP was assessed at ’hours’ in 5 studies (42,56,66,81,83), at ’days’ in 3 studies (42,63,93), at ’weeks’ in 2 studies (42,66), and at ’months’ in 3 studies (63,88,92) ( Fig. 4C ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations